ChM. Ts. Dr. Siti Qurratu’ Aini develops Green Shale Swelling Inhibitor for shale swelling in the oil and gas industry - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 17 July 2025 – Concerns over environmental pollution caused by the use of non-environmentally friendly chemicals in the oil and gas industry became the starting point for the development of an eco-friendly formulation to replace the use of potassium chloride (KCl) in drilling operations.